Dampak Objek Wisata Patung Tuhan Yesus Terhadap Kehidupan Sosial Ekonomi Masyarakat Sekitar Buntu Burake di Kecamatan Makale Kabupaten Tana Toraja - Bai’ru, Frelia Natali Refi; Kapile, Charles (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2022)
Research on the Impact of the Statue of the Lord Jesus Statue Tourism on the socio-economic life of the communities around Burake Hill in Makale District of Tana Toraja Regency. The research method used was the descriptive method with a qualitative approach. Data collection techniques were done through observation, interviews, and documentation. The results of this research indicate that the socio-economic conditions of the community with the existence of tourism that is the community initially only worked as Construction laborers, housewives, farmers, and even some who do not have jobs or are unemployed. The existence of tourism objects provides a huge opportunity for the community to jump into the tourism sector, some of them work as tourist object managers (levies collectors), Parking Officers, and some work as sellers/traders, then they automatically get income. Income generated is that if a tourist attraction is crowded, the community income is around IDR. 200,000 - IDR. 600,000 and if the tourism is empty, the community's income is around IDR. 100,000 – IDR. 300,000. The tourism of the statue of the Lord Jesus had an impact on the socio-economic conditions of the communities around Burake Hill such as opening up employment opportunities, increasing the income of the community and also the government, and the impact on development.